Ocidentalização, territórios e populações indígenas no sertão da Capitania do Rio Grande - Macedo, Helder Alexandre Medeiros de (2007)
The objective of this work is to understand some of the modifications caused for the phenomenon of the westernization in the hinterland of the Capitania do Rio Grande e in the life of the indians populations that inhabited there during the Colonial Period. We break of the quarrel of Serge Gruzinski concerning the westernization, understood while immersed phenomenon in the context of the expansion of the commercial capitalism and that, for the imposition of the culture occidental person to the alteridades of the New World, emprende the conquest of its territories, bodies and souls. The space clipping has covered the hinterland of the Capitania do Rio Grande, specifically the colonial territory of the Freguesia da Gloriosa Senhora Santa Ana do Seridó. The chosen chronological limit for the research corresponds to the Colonial Period and part of the Imperial one. However, the emphasis falls again on the period that it initiates in 1670, year of the oldest concession of would sesmaria known until the moment in the hinterland of the Rio Grande, extending itself until the decade of 1840. Sources of written by hand nature, cartographic printed and compose the used document roll: official correspondence and legislation, petitions of would sesmaria, inventories post-mortem, justifications of debt, registers of parish, maps, action civil court jurisdiction, notes of notary's office, land landmarks. We take the method, analyzed for Carlo Ginzburg, to cross these sources between itself and to detect its implied particularitities and ideas in the space between lineses, but, attributing it status to they of a colonial speech, fruit of the bureaucracy of where it was originated and of the social place of who produced it. We look for to demonstrate, throughout the work, that the phenomenon of the westernization desestruturou the aboriginal societies and its habitat, constructing, over its rubbles, a colonial territory that found in the cartography of the Freguesia de Santa Ana an efficient instrument of control of the space and the population. On the other hand, if the imposition of the culture occidental person exterminou great part of the native population that inhabited the hinterland of the Rio Grande, the remainders of these indians and the mestizos of descending them had survived in diverse ways in the freguesia: in the condition of captives of war or in regimen of servile work, as living or assistants in the farms, populations and village; rambling without route in the fields and the population spots; as mediating agents between the world occidental person and the native, exerting military or civil positions and still appealing to Justice in search of its rights of inheritance. Experiences of slavery, servitude, errância and mediation, but, also of resistance, adaptation, mestization in the Freguesia de Santa Ana